"Redevelopment of catalysts used in acetaldehyde synthesis and creation of new catalysts” (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This article discusses the need to be synthesized from acetaldehyde methane raw materials at Navoiyazot JSC in the presence of a KKF (cadmium calcium phosphate) catalyst in the process of acetylene hydration, and the need for processing due to the fact that this catalyst is imported at the expense of currency, and taking into account the fact that the used catalyst